A Study of Late Postpartum Eclampsia - 178 Cases - Habib, Sahin Akhter Jahan; Sultana, Sayeeda (Bangladesh Medical Journal, 2009)
Objective: The purpose of this study was to determine whether there is a shift in the timing of eclampsia in relation to delivery and whether traditional symptoms precede impending postpartum eclampsia. Study Design: A cross - sectional hospital - based study conducted at Gynae Unit, Dhaka Medical College Hospital from January 2006 - December 2007. Data was collected regarding the relationship of the patient's first seizure to delivery prodromal symptoms, neuroimaging studies, use of magnesium sulfate, antihypertensive therapy and follow up medical care. The analysis focused on women who had late postpartum eclampsia. Result: During the study period 178 patients were diagnosed with eclampsia. Fifty eight women (33%) had postpartum eclampsia, of which 46 women (79%) had late onset (> 48 hrs.). Interestingly only 10 of these 46 women (22%) had been previously diagnosed with preeclampsia. Forty two pt.(91%) with late postpartum eclampsia had at least 1 prodromal symptom, and 24 pt. (52%) had> 1 symptom that heralded the seizure : 40 women (87%) had headache , 20 women (44%) had visual changes, 10 (22%) had nausea or vomiting and 4 (9% ) experienced epigastric pain. Only 14 of this 42 women (33%) sought care for their symptoms , of whom 12 women (86%)had clinical evidence of preeclampsia that was not considered by the treating physician. Among all patients with eclampsia there were 14 cases of aspiration pneumonia,6 cases of pulmonary edema, 6 cases of pleural effusion 4 cases of DIC and no cases of maternal death. Conclusion: Current obstetric treatment has a resulted in a shift of eclampsia toward the postpartum period with most cases being seen as late postpartum. To reduce the rate of the postpartum eclampsia, efforts should be directed to the education of the health care providers and patients regarding the importance of prompt reporting and evaluation of symptoms of preeclampsia during the postpartum period. DOI: 10.3329/bmj.v37i2.3594 Bangladesh Medical Journal 37(2) 2008 52-55